(3GdYdGbGJ GdOhdjI Hjf GdYhdeI hGdCeQcI (B/s - (3egfG, eMeO fUQs ((3GdGScfOQjI(B: s (3GdecJH GdLGeYj GdMOjK(B, s, 2006)
(3jVe eG bHd GdYhdeI aj Yde GdYdGbGJ GdOhdjI, efGgL GdHMK, eaGgje CSGSjI, GdGeHQjGdjI hGdGSJYeGQ GdLOjO, CHYGO Yde GdYdGbGJ GdOhdjI, GdOhdI hJGQjN SjGSI JhGRf Gdbhi, GdOhdI hGdefXeGJ ZjQ GdMchejI aj GdeeGQSGJ GdOhdjI, GdGSJbdGd heHOC YOe GdJONd aj GdTDhf GdOGNdjI ddOhd, SjGSI JhGRf Gdbhi, GdYdGbGJ GdOhdjI ef GdJbdjOjI Gdi GdeYGUQI(B: (3eXGgQ eeGQSI GdYdGbGJ GdOhdjI, GdSjGSI GdNGQLjI, fMh fXGe YGdej LOjO, GdOHdheGSjI, GdJLOjO aj Yde GdYdGbGJ GdOhdjI, GfgjGQ GdbWHjI GdKfGFjI heGHYOgG, aj GdfXGe GdYGdej GdLOjO, GdeJZjQGJ GdeYGUQI aj GdYdGbGJ GdOhdjI, GdYhdeI hGdCeQcI, GdYhdeI Hjf GdacQ hGdJWHjb, GdCeQcI hcjajI ehGLgJgG(B.s
Keywords: (3GdYdGbGJ GdEbJUGOjI GdOhdjIs; (3GdYdGbGJ GdNGQLjIs; (3GdYhdeIs